2018
DOI: 10.1029/2018jd029228
|View full text |Cite
|
Sign up to set email alerts
|

How Do Weak Tropical Cyclones Produce Heavy Rainfall When Making Landfall Over China

Abstract: In this study, we investigate rainfall characteristics, such as rainfall intensity, rainfall coverage, and the location of heavy rain, associated with tropical cyclones (TCs) that made landfall over China during 2005-2014, using the observations of Tropical Rainfall Measuring Mission and environmental fields. Results show that before landfall, the stronger the TC itself is, the stronger the TC rainfall intensity is in both eyewall and inner rainband regions. However, there is no obvious difference in rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
(112 reference statements)
3
10
0
Order By: Relevance
“…Consistent with the result of Wang (2012) for cyclogenesis, our analysis shows that the midlevel DAI is favorable to the generation of stratiform precipitation through producing moderate midlevel convergence and less intense low‐level subsidence which contribute to the midlevel spin‐up without spinning down the low‐level circulation, or help maintaining the uniform stratiform precipitation above the melting layer and homogenizing the low‐level circulation, and thus boosts the development of stratiform precipitation in intensity or areal coverage. The results obtained here deepen the previous finding by Feng and Shu (2018), which showed that the total precipitation in the outer region does not change much as that in the eyewall during TC landfall without providing scientific explanation. Since the stratiform precipitation is found to occur when the young and vigorous convection becomes older or mature (Houze, 1997), the results of this work seems to indicate that the DAI may speed up the lifecycle of the convective system or trigger the transition from convective precipitation to stratiform precipitation.…”
Section: Summary and Discussionsupporting
confidence: 87%
“…Consistent with the result of Wang (2012) for cyclogenesis, our analysis shows that the midlevel DAI is favorable to the generation of stratiform precipitation through producing moderate midlevel convergence and less intense low‐level subsidence which contribute to the midlevel spin‐up without spinning down the low‐level circulation, or help maintaining the uniform stratiform precipitation above the melting layer and homogenizing the low‐level circulation, and thus boosts the development of stratiform precipitation in intensity or areal coverage. The results obtained here deepen the previous finding by Feng and Shu (2018), which showed that the total precipitation in the outer region does not change much as that in the eyewall during TC landfall without providing scientific explanation. Since the stratiform precipitation is found to occur when the young and vigorous convection becomes older or mature (Houze, 1997), the results of this work seems to indicate that the DAI may speed up the lifecycle of the convective system or trigger the transition from convective precipitation to stratiform precipitation.…”
Section: Summary and Discussionsupporting
confidence: 87%
“…As TCs approach the coast (preland TCs), the rainfall magnitude experiences a slight decrease by about 3%, which is consistent with previous studies [32,37,42]. e contribution from higher wavenumbers to the total rainfall of preland TCs is slightly higher than that of off-shore TCs.…”
Section: Rainfall Contribution Spectrumsupporting
confidence: 91%
“…However, TC rainfall enhancement induced by topographic effect was not evident in other landfalling TC studies [32,42]. Feng and Shu [37] showed that TC experienced a decrease in rainfall intensity during its landfall due to the cutting-off of energy and moisture from the ocean. In contrast, TC rainfall redistribution can be promoted by the interaction between a TC and baroclinic systems.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies show that landfalling tropical cyclones can make great contributions to extreme rainfall in inland regions, even though the frequency of occurrence is not as comparative as coastal regions (e.g., Zhang et al, 2018a). This is closely linked to a couple of factors, such as the interplay of tropical cyclone and baroclinic disturbances (i.e., known as extratropical transition, Hart and Evans, 2000), interactions with mid-latitude systems (e.g., easterly, Shu et al, 2018;Feng and Shu, 2018), and impact of regional topography (as demonstrated by Typhoon Nina, Yang et al, 2017). The devastating consequences of Typhoon Nina and the August 1975 flood expose inadequacies of conventional approaches for flood frequency analysis (e.g., fitting historical flood records with assumed distribution function), and highlight the importance of hydrometeorological approaches for Probable Maximum Precipitation (PMP) / Probable Maximum Flood (PMF) analyses for better designs of flood-control infrastructures (e.g., Smith and Baeck, 2015;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%